2003
DOI: 10.2105/ajph.93.9.1509
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Safe Walking and Cycling to Improve Public Health: Lessons From The Netherlands and Germany

Abstract: A wide range of measures are available to improve the safety of walking and cycling in American cities, both to reduce fatalities and injuries and to encourage walking and cycling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
356
2
17

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 647 publications
(388 citation statements)
references
References 13 publications
13
356
2
17
Order By: Relevance
“…The British Department of Transport, for example, found that the risk of pedestrian death in crashes rises from 5% at 20 mph to 45% at 30 mph and 85% at 40 mph. 4 The link between speed and road trauma is clear in the road safety literature, even for minor changes in speed. Increasing traffic speeds by only 1 km/h can lead to a 3% increase in injury crashes and a 4-5% increase in fatal crashes.…”
Section: Existing Understandings Of the Links Between Speed And Healthmentioning
confidence: 99%
“…The British Department of Transport, for example, found that the risk of pedestrian death in crashes rises from 5% at 20 mph to 45% at 30 mph and 85% at 40 mph. 4 The link between speed and road trauma is clear in the road safety literature, even for minor changes in speed. Increasing traffic speeds by only 1 km/h can lead to a 3% increase in injury crashes and a 4-5% increase in fatal crashes.…”
Section: Existing Understandings Of the Links Between Speed And Healthmentioning
confidence: 99%
“…The US has a notoriously poor safety record relative to other developed countries. According to a study by Pucher and Dijkstra (2003), after controlling for travel exposure in terms of mileage, US pedestrians (cyclists) are roughly 3 times (2 times) more likely to get killed in traffic accidents than German pedestrians (cyclists) and over 6 times (3 times) more likely than Dutch pedestrians (cyclists). Pucher and Dijkstra also compared fatality rates per mile of travel by different modes in the US, and concluded that pedestrians were 23 times more likely to get killed than car occupants, and bicyclists were 12 times more likely.…”
Section: Introductionmentioning
confidence: 99%
“…In cross-country comparisons, Pucher and Dijkstra (2003) found that, after controlling for travel exposure in terms of mileage, U.S. pedestrians (bicyclists) are about 3 times (2 times) as likely to get killed in traffic accidents as German pedestrians (bicyclists) and over 6 times (3 times) as likely to be killed as Dutch pedestrians (bicyclists). In another more recent study at a metropolitan area level (rather than a national level that can mask risk variation within countries), McAndrews (2011) observed that the risk of a fatal traffic crash injury for pedestrians in San Francisco is 4.1 times higher than for pedestrians in Stockholm, while the corresponding figure is 1.7 for bicyclists.…”
mentioning
confidence: 99%